Advances in the role of exosomal non-coding RNA in the development, diagnosis, and treatment of gastric cancer (Review) - Gao, Peng-Fei (Mol Clin Oncol, 2020)
Exosomes are small vesicles secreted by a variety of cells that contain vrious biological macromolecules, including RNA, non-coding RNA and protein. An increasing number of studies have demonstrated that exosomes and particularly the non-coding RNAs they contain, serve important roles in many cellular processes, including the transmission of information. It is well established that the occurrence and development of gastric cancer, one of the four most common malignant tumors worldwide, involves the transmission of information. Based on the urgent need for the elucidation of the mechanism involved in this process, as well as advances in the diagnosis and treatment of gastric cancer, numerous reports have assessed the association between non-coding RNAs in exosomes and gastric cancer. The purpose of the present review was to summarize recent evidence on certain non-coding RNAs associated with the development, diagnosis and treatment of gastric cancer.